2022
DOI: 10.3390/fractalfract6110678
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Mode Control for a Class of Nonlinear Fractional Order Systems with a Fractional Fixed-Time Reaching Law

Abstract: In this paper, the sliding-mode control method was used to control a class of general nonlinear fractional-order systems which covers a wide class of chaotic systems. A novel sliding manifold with an additional nonlinear part which achieved better control performance was designed. Furthermore, a novel fixed-time reaching law with a fractional adaptive gain is proposed, where the reaching time to the sliding manifold is determined by the first positive zero of a Mittag–Leffler function and is independent of ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The findings of the research were reported in [32], and one of the main takeaways was the development of a new synchronized fixed-time TSM technique for use with fractional chaotic systems. The authors in [33] suggested a non-singular fixed-time sliding mode method as a solution to the non-linear chaotic system. In order to better accommodate scattered quadrotors, an improved adaptive fractional-order rapid integral TSMC was devised [34].…”
Section: Related Workmentioning
confidence: 99%
“…The findings of the research were reported in [32], and one of the main takeaways was the development of a new synchronized fixed-time TSM technique for use with fractional chaotic systems. The authors in [33] suggested a non-singular fixed-time sliding mode method as a solution to the non-linear chaotic system. In order to better accommodate scattered quadrotors, an improved adaptive fractional-order rapid integral TSMC was devised [34].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, fractional-order (Fo) control has been incorporated with SMC to improve the performance of the controller [21][22][23]. Fractional-order control, which has been in use for the last three centuries and is concerned with derivatives and integrals of a non-integer order, was recently rediscovered by scientists and engineers and is being put to use in a variety of different fields [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional-order differential equations, which are actually generalizations of integer order calculus, deal with derivatives and integrals with non-integer orders. These equations have a unique feature which is the description of the memory effect [6][7][8]. Fractional derivative chaotic systems are now an important topic of study in nonlinear dynamics.…”
Section: Introductionmentioning
confidence: 99%